Tiger (Panthera tigris tigris) Crisis in the Western Rajaji National Park - Rishi, Vinod (Indian Forester, 2012)
The western part of the Rajaji National Park is the north-western limit of distribution of the Indian tiger in the world. Recent reports on the status of tigers in India indicates that the population in this part is threatened with imminent extinction since the all three tigers are females geographically and genetically isolated from the rest of tiger population in the National Park. Such situations exist in many parts of India and the paper discusses the crisis and suggests management intervention that may be used as a tool to overcome such critical situations in tiger conservation in India.